2015
DOI: 10.1007/s12094-015-1289-8
|View full text |Cite
|
Sign up to set email alerts
|

High pretreatment neutrophil–lymphocyte ratio predicts recurrence and poor prognosis for combined small cell lung cancer

Abstract: High pretreatment NLR (≥4.15) is a potential useful indicator for C-SCLC recurrence and predicts a poor long-term prognosis for C-SCLC, which should be considered in defining the prognosis with other well-known prognosticators in C-SCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 31 publications
10
37
0
Order By: Relevance
“…In this study, we found that the increased levels of NLR and PLR were associated with worse clinical outcome, which was consistent with the previous studies (25,26), although the role of inflammation cell in the tumor pathogenesis was not fully elucidated.…”
supporting
confidence: 92%
“…In this study, we found that the increased levels of NLR and PLR were associated with worse clinical outcome, which was consistent with the previous studies (25,26), although the role of inflammation cell in the tumor pathogenesis was not fully elucidated.…”
supporting
confidence: 92%
“…The characteristics of the 18 studies are summarized in Table I. A total of 7 studies were conducted in Western countries, including the UK (17,26,34), USA (28), Spain (20) and Italy (22,34), 1 study was performed in Turkey (23), and 10 studies were performed in East Asian countries, including Japan (18,19,31,32), Korea (21,25) and China (24,27,30,33). The study published by Mitchell et al (29) included patient data from 33 countries.…”
Section: Resultsmentioning
confidence: 99%
“…The study published by Mitchell et al (29) included patient data from 33 countries. The included studies evaluated 16 populations of patients with NSCLC (17-24,26-29,31-34) and 2 populations of patients with SCLC (25,30). The 2 studies on SCLC reported tumor staging information as limited and extensive disease, so only the staging information from the studies regarding NSCLC were considered Only 1 study by Sarraf et al (17) evaluated all tumor stages, 8 studies evaluated early-stage tumors (23,(26)(27)(28)(29)(31)(32)(33), and 6 studies evaluated late-stage tumors (18,(20)(21)(22)24,34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that a systemic inflammatory state is associated with the malignant biological behavior of the tumor (14,15). In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)). An elevated NLR has already been shown to be associated with poor prognosis in patients with HCC treated by liver transplantation, surgical resection, or TACE (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%